Examining physical and technical performance among youth basketball national team development program players: a multidimensional approach - Kazimierz Mikołajec; Jorge Arede; Karol Gryko (Scientific Reports)
Abstract This study aimed to examine and compare the anthropometric profiles, motor skills, game-related abilities, and functional capacities of under-15 (U-15) and under-16 (U-16) male basketball players, evaluate the impact of maturity offset, and predict performance across physical and sport-specific domains. A total of 234 athletes participated in a comprehensive test battery, assessing morphological (height, mass, standing reach), physical (sprinting, agility, jump height, endurance), technical (jump shot, free throws, dribbling), and functional movement screen variables. The U-16 group outperformed U-15 players in physical characteristics and jump height. Within the U-15 group, players with advanced maturity exhibited greater body mass, height, reach, and vertical jump performance. Maturity offset was a significant predictor of linear speed and standing jump, while factors like age, height, and functional abilities contributed to broader physical performance outcomes. Only height and FMS scores were associated with sport-specific skill levels. These findings highlight that a multidimensional approach—including maturity status, anthropometric data, physical and technical skills, and functional assessments—provides essential insights for supporting athletic development in young basketball players and can inform tailored training strategies to enhance both physical and technical performance.